Adjuvant radiotherapy-induced cardiac changes among patients with early breast cancer: a three-year follow-up study*. (2nd September 2019) - Skyttä, Tanja; Tuohinen, Suvi; Luukkaala, Tiina; Virtanen, Vesa; Raatikainen, Pekka; Kellokumpu-Lehtinen, Pirkko-Liisa
Abstract: Background: In this study, we evaluate the evolution of cardiac changes during a three-year follow-up after adjuvant breast radiotherapy (RT). Methods: Sixty patients with left-sided and 20 patients with right-sided early stage breast cancer without chemotherapy were included in this prospective study. Echocardiography and cardiac biomarkers were evaluated before, immediately after and 3 years after RT. Radiation doses to cardiac structures were calculated. Results: In echocardiography, left ventricle (LV) systolic measurements had impaired at 3 years compared to baseline: the mean global longitudinal strain (GLS) worsened from –18 ± 3 to –17 ± 3 ( p  = .015), LV ejection fraction from 62 ± 5% to 60 ± 4% ( p  = .003) and the stroke volume from 73 ± 16 mL to 69 ± 15 mL ( p  = .015). LV diastolic function was also negatively affected: the isovolumetric relaxation time was prolonged ( p  = .006) and the first peak of diastole decreased ( p  = .022). Likewise, left atrial (LA) measurements impaired. These changes in echocardiography were more prominent in left-sided than in right-sided patients. The concurrent aromatase inhibitor (AI) use was associated with GLS impairment. In all patients, the N-terminal pro-brain natriuretic peptide (proBNP) values were median (interquartile range) 74 (41–125) ng/L at baseline, 75 (41–125) ng/L at the end of RT and 96 (56–162) ng/L at 3 years ( p  < .001 from baseline to 3 years). However, proBNP did not increase in right-sided patients. Conclusion: During the 3-year follow-up after RT, negative subclinical changes in cardiac biomarkers and in LV systolic and diastolic function were observed. The measured changes were more pronounced in left-sided patients. In addition, AI use was associated with impaired cardiac systolic function.